Characterization of solid char produced from pyrolysis of the organic fraction of municipal solid waste, high volatile coal and their blends - Tokmurzin, Diyar; Kuspangaliyeva, Botagoz; Aimbetov, Berik; Abylkhani, Bexultan; Inglezakis, Vassilis J.; Anthony, Edward J.; Sarbassov, Yerbol (Elsevier, 2019)
In this study, the organic fraction of municipal solid waste (Org-MSW) was blended with high-volatile coal (HVC) in proportions of 25/75%, 50/50%, 75/25% by weight. Pyrolysis of these mixtures was then investigated in a thermogravimetric analyzer (TGA) and a horizontal tube furnace under a nitrogen environment. The mass loss rate of samples, differential thermogravimetry (DTG) curves and kinetic analysis of the samples were compared for both blended and non-blended samples. Higher gas yields were seen with increasing pyrolysis temperature for both samples. In addition, the kinetic analysis indicated that the apparent activation energy values of org-MSW samples varied from 535 to 5284 kJ/kmol (over the temperature range of 100–887 °C), while the values for HVC were 247–962 kJ/kmol. The activation energy for HVC varied with temperature and the highest value of 2036 kJ/kmol was found in the temperature range of 336–490 °C. Comparable results were obtained between the TGA and fixed bed tests on the residual char fraction. The findings of this work will be very important in developing a co-firing technology for solid waste residuals and coal for energy production.
Keywords: Pyrolysis; Organic waste; High volatile coal; Char characterization